Alat Virtual Assistant Untuk Membantu Treatment Pasien Patah Tulang Kaki - Tony Tony; Budianto Lomewa Lo; Chairisni Lubis (UIN Sultan Syarif Kasim Riau, 2012)
Broken leg bone is one of the conditions which must be dealt with immediately emergency quickly, appropriately and in accordance with applicable procedures. In the design of a virtual assistant to help tool treatment patient fractures foot, accelerometer sensor is used to detect boundary slope foot raised by patients. When the tool is run, the microcontroller will run a program that has been input and accelerometer sensor will detect the tilt foot limit would be appointed by the patient. In addition to the sensor, which also serves to display the LCD schedule medication as well as exercise treatment foot fracture patients and buzzer that serves as a warning sound when the schedule is on medication and exercise treatment foot fracture patients the time has come. If the process of treatment of fractures leg exercises are over, then press button ok to terminate the program. Test results show overall tool can run with either starting from warning alarm in reminding patients to take medication until the accelerometer sensor in detecting limit the slope foot raised by patients in their healing process.Keywords: virtual assistant, microcontroller, accelerometer sensor